Mini-review: Lipid flippases as putative targets for biotechnological crop improvement - López-Marqués, Rosa Laura (Frontiers in Plant Science, 2023)
An increasing world population and drastic changes in weather conditions are challenging agricultural production. To face these challenges and ensure sustainable food production in the future, crop plants need to be improved to withstand several different biotic and abiotic stresses. Commonly, breeders select varieties that can tolerate a specific type of stress and then cross these varieties to stack beneficial traits. This strategy is time-consuming and strictly dependent on the stacked traits been genetically unlinked. Here, we revise the role of plant lipid flippases of the P4 ATPase family in stress-related responses with a special focus on the pleiotropic nature of their functions and discuss their suitability as biotechnological targets for crop improvement.